Role of the IL8 rs4073 polymorphism in central nervous system toxicity in patients receiving multidrug-resistant tuberculosis treatment - Mohammed Badamasi, Ibrahim; Muhammad, Muktar; Umar, Aishat Ahmad; Madugu, Umm-Ayman Misbahu; Gadanya, Muktar Ahmed; Aliyu, Isa Abubakar; Kabir, Imam Malik; Umar, Ibrahim Aliyu; Johnson, Ochigbo; Stanslas, Johnson (Sociedade Brasileira de Pneumologia e Tisiologia, 2024)
Objective: To determine the role of the IL8 rs4073 polymorphism in predicting the risk of central nervous system (CNS) toxicity in patients receiving standard pharmacological treatment for multidrug-resistant tuberculosis (MDR-TB). Methods: A cohort of 85 consenting MDR-TB patients receiving treatment with second-line antituberculosis drugs had their blood samples amplified for the IL8 (rs4073) gene and genotyped. All patients were clinically screened for evidence of treatment toxicity and categorized accordingly. Crude and adjusted associations were assessed. Results: The chief complaints fell into the following categories: CNS toxicity; gastrointestinal toxicity; skin toxicity; and eye and ear toxicities. Symptoms of gastrointestinal toxicity were reported by 59 of the patients, and symptoms of CNS toxicity were reported by 42.7. With regard to the genotypes of IL8 (rs4073), the following were identified: AA, in 64 of the study participants; AT, in 7; and TT, in 11. A significant association was found between the dominant model of inheritance and CNS toxicity for the crude model (p = 0.024; OR = 3.57; 95 CI, 1.18-10.76) and the adjusted model (p = 0.031; OR = 3.92; 95 CI, 1.13-13.58). The AT+TT genotype of IL8 (rs4073) showed a 3.92 times increased risk of CNS toxicity when compared with the AA genotype. Conclusions: The AT+TT genotype has a tendency to be associated with an increased risk of adverse clinical features during MDR-TB treatment.